Формативное оценивание знаний учащихся на уроках физики - Аубакирова, А.А. (My University, 2016)
In terms of new educational program it is essential to know how well students learn current educational material. The article gives examples from the experience of the teacher by conducting learners’ educational formative assessment of the physics subject and using assessment sheets.
Keywords: formative assessment; criteria for success; skills; physics; evaluation sheet; reached seeks